(untitled) (The Voz a Vos Bulletin, 2026)
This text, was written in order to be interpreted as a lecture accompanied by performative gestures, it reflects on the relationship between body, city, and scenic practice through the research-creation process Tacto con-tacto, developed within the research group Técnica y utopía. In dialogue with contemporary thought, the project addresses issues such as hypercommunication and the naturalization of violence in everyday urban life. Through the training of techniques such as Suzuki, Viewpoints, and contact improvisation, the group proposes performative actions that interrupt urban routines and temporarily resignify public space. The process reveals the creative potential that emerges from exploring the body as both individual and relational within urban dynamics that often privilege productivity over affect, proximity, and physical contact.